Kinerja gateway berbasis XMPP untuk komunikasi perangkat IoT - Mahar Faiqurahman; Muhammad Malik Madani; Denar Regata Akbi (Jurnal Teknologi dan Sistem Komputer, 2019)
This study examines the performance of a communication gateway for IoT devices by utilizing the XMPP protocol so that these devices can be connected and communicate using the Internet. The sensor nodes, which are IoT devices, were implemented using NodeMCU connected to the DHT11 sensor module and LED lights to simulate the incoming data. Sensor nodes can communicate using the XMPP protocol gateway and process the request-response data. Gateway data transmission performance with size variations from 10-100 MB gets an average delay time of 9.3 ms, an average jitter of 0.00178 ms, and an average throughput of 161.4 kbps. The CPU usage parameter has an average increase of 12%, and memory usage tends to be constant when data transmission occurs.